The complete chloroplast genomes of two Pedicularis species (Orobanchaceae) from Southwest China. Issue 6 (3rd June 2022) - Wang, Wei-Jia; Liu, Rong; Wu, You; Wang, Hong; Yu, Wen-Bin
Abstract: We report the complete chloroplast genome (plastome) sequences of Pedicularis cephalantha (147, 087 bp) and P. nigra (145, 726 bp), endemic to southwestern China. Both plastomes have typical quadripartite structures with one large-single copy region, one small-single copy region, and two inverted repeat regions. Both plastome sequences contained 37 tRNA genes and eight rRNA genes, but they differed in the numbers of protein-coding genes: P. cephalantha had 76 functional genes and 12 pseudogenes while P. nigra had 74 functional genes and 13 pseudogenes. Phylogenetic analysis shows that P. cephalantha and P. nigra are closely related, then sister to P. oederi in the family Orobanchaceae.